Abstract Reality: The Alienating Gaze - Matheson, Clare (Auckland University of Technology, 2007)
This is a visual arts project consisting of 20% exegesis and 80% practical work. My work explores the visual possibilities of using the digital accumulation of data to convey socio-political concepts in relation to the surveillance of the individual in modern western society. The nature of surveillance is investigated with reference to Michel Foucault's metaphorical use of Jeremy Bentham's panopticon in describing the organization of society in the modern nation state. My critical interest lies in the intrusive aspect of surveillance in regard to the privacy of the individual and the concomitant sense of alienation and disempowerment. The concept of 'abstract reality' has been developed to describe the nature of the surveillance of the individual in the modern nation state.
Keywords: Surveillance; Panopticon; Privacy; Heuristic; Foucault; Society